Low-cost, open-source XYZ nanopositioner for high-precision analytical applications. (April 2022) - Liao, Hsien-Shun; Werner, Christian; Slipets, Roman; Emil Larsen, Peter; Hwang, Ing-Shouh; Chang, Tien-Jen; Ulrich Danzebrink, Hans; Huang, Kuang-Yuh; Hwu, En-Te
Graphical abstract: Abstract: Nanoscale positioning has numerous applications in both academia and industry. A growing number of applications require devices with long working distances and nanoscale resolutions. Friction–inertia piezoelectric positioners, which are based on the stick–slip mechanism, achieve both nanometer resolution and centimeter-scale travel. However, the requirements of complex preload mechanism, precision machining, and precise assembly increase the cost of conventional friction–inertia nanopositioners. Herein we present the design of an open-source XYZ -axis nanopositioning system. Utilizing a magnet-based stick–slip driving mechanism, the proposed XYZ nanopositioner provides several advantages, including sub-nanometer resolution, a payload capacity of up to 12 kg (horizontal), compact size, low cost, and easy assembly; furthermore, the system is adjustment-free. The performance tests validate the precision of the system in both scanning and stepping operation modes. Moreover, the resonant spectra affirm the rigidity and dynamic response of the mechanism. In addition, we demonstrate the practical applications of this nanopositioner in various measurement techniques, including scanning electron microscopy, vibrometry, and atomic force microscopy. Furthermore, we present 11 variations of the nanopositioner designs that are either compatible with ultra-high-vacuum systems and other existing systems, 3D printable, or hacking commercial linear slides.